2022
DOI: 10.3389/fpubh.2022.942377
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral treatment in outpatients with herps zoster in six major areas of China, 2010–2019

Abstract: ObjectiveThe objective of this study was to assess the status and trends of antiviral treatment in outpatients with herpes zoster in China.MethodsPrescription data on antiviral drugs were extracted from the database of the Hospital Prescription Analysis Program of China according to the inclusion criteria. Yearly prescriptions and costs were calculated, and trends were analyzed. The trends were further stratified by age, sex, and specific drug use. The distribution of defined daily costs (DDCs) of valaciclovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…HPACP is a national multi-center hospital prescription database [ 38 46 ]. Each participating hospital randomly selects ten days from its prescription information and uploads it to this database every quarter.…”
Section: Methodsmentioning
confidence: 99%
“…HPACP is a national multi-center hospital prescription database [ 38 46 ]. Each participating hospital randomly selects ten days from its prescription information and uploads it to this database every quarter.…”
Section: Methodsmentioning
confidence: 99%
“…33 Studies have shown that the main antiviral drugs currently used in clinical practice for HZ are valacyclovir and famciclovir, while the frequency of acyclovir use is gradually decreasing. 34 Acyclovir was first mentioned in 1974 by Nick Oliver 35 and then its antiviral properties were first discovered by Peter Collins and John Bauer of Wellcome Laboratories in Beckenham, the UK. 36 The anti-herpetic activity of acyclovir is achieved by inhibition of herpes-specific replicative DNA polymorphases.…”
Section: Drug Therapymentioning
confidence: 99%